SCREENING OF VEGETABLES FOR PHYTOEXTRACTION OF HEAVY METALS - Kafle, Baby Sharma (Ecoprint: An International Journal of Ecology, 2014)
To understand the phytoextraction of heavy metals from contaminated soil, eighteen seasonalvegetable crops were investigated. The soil was artificially contaminated each with 300 mg kg-1CuCl2, 500 mg kg-1 Pb (NO3)2, 800 mg kg-1 ZnCl2 or their mixed metal (1600 mg kg-1). Lowestcopper (Cu) accumulation was recorded in Brassica juncea and highest in Vicia faba, while lowestlead (Pb) accumulation in Solanum tuberosum, and highest in Allium fistulossum; and lowest zinc(Zn) accumulation in both Allium fistulossum and Solanum tuberosum, and highest was in Vicia fabafrom the single metal contamination. Similarly, lowest Cu, Pb and Zn was recorded in Brassicajuncea, Brassica caulorapa and Allium fistulossum, respectively; and highest accumulation of Cu andPb was in Spinacea oleracea and Zn in Spinacea oleracea from their mixed metal treatments. DOI: http://dx.doi.org/10.3126/eco.v20i0.11469 ECOPRINT An International Journal of Ecology Vol. 20, 2013 page: 81-88